The application of CAR-T cell therapy in hematological malignancies: advantages and challenges - Zijun Zhao; Yu Chen; Ngiambudulu M. Francisco; Yuanqing Zhang; Minhao Wu (Elsevier, 2018)
Chimeric antigen receptor T cell (CAR-T cell) therapy is a novel adoptive immunotherapy where T lymphocytes are engineered with synthetic receptors known as chimeric antigen receptors (CAR). The CAR-T cell is an effector T cell that recognizes and eliminates specific cancer cells, independent of major histocompatibility complex molecules. The whole procedure of CAR-T cell production is not well understood. The CAR-T cell has been used predominantly in the treatment of hematological malignancies, including acute lymphoblastic leukemia, chronic lymphocytic leukemia, lymphoma, and multiple myeloma. Solid tumors including melanoma, breast cancer and sarcoma offer great promise in CAR-T cell research and development. CD19 CAR-T cell is most commonly used, and other targets, including CD20, CD30, CD38 and CD138 are being studied. Although this novel therapy is promising, there are several disadvantages. In this review we discuss the applications of CAR-T cells in different hematological malignancies, and pave a way for future improvement on the effectiveness and persistence of these adoptive cell therapies. KEY WORDS: Chimeric antigen receptor T cell, Clinical applications, Immunotherapy, Malignancies